2021
DOI: 10.54589/aol.34/3/240
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cone-beam computed tomography, clinical and surgical analysis for detection of maxillary molar furcation

Abstract: The aim of this study was to compare the performance of conebeam computed tomography (CBCT), clinical and surgical probing in assessing maxillary molar furcation involvement (FI). Furcation defects (n= 120) were assessed through CBCT, clinical and intra-surgical evaluation (ISE). Furcation Involvement, vertical and horizontal bone loss were assessed through clinical probing, CBCT and probing during ISE. Three trained radiologists evaluated CBCT images and intra- and interobserver agreement were calculated by K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(76 reference statements)
0
0
0
Order By: Relevance
“…Evidence suggests that detailed information of furcation involvement was given by the CBCT images of maxillary molars with an 82.4% intra-surgical accuracy [5,8]. Recent studies have however concluded that diagnosis of incipient furcation lesions was still best made using clinical evaluation [9].…”
Section: Furcation Involvementmentioning
confidence: 99%
“…Evidence suggests that detailed information of furcation involvement was given by the CBCT images of maxillary molars with an 82.4% intra-surgical accuracy [5,8]. Recent studies have however concluded that diagnosis of incipient furcation lesions was still best made using clinical evaluation [9].…”
Section: Furcation Involvementmentioning
confidence: 99%